Comparative efficacy of acupuncture-related techniques for mild cognitive impairment: A Bayesian network analysis - Li, Xin; Lai, Lanfeng; Lu, Liming; Yan, Liang; Deng, Kelin; Li, ZhiMing; Xu, Nenggui; Zhao, JiaYing (Frontiers in Neurology, 2022)
Background A comparison and ranking of the clinical effects of various acupuncture and acupuncture-related therapies on patients with mild cognitive impairment. Methods Using network meta-analysis, we assessed the direct and indirect evidence from relevant research. Seven databases [PubMed, Web of Science, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), VIP Database, and Wanfang database] were examined to find randomized controlled trials of acupuncture-related therapies for individuals with mild cognitive impairment. Two researchers independently reviewed the literature, retrieved the data, and evaluated the risk of bias in the included studies. The data were analyzed using Stata15.0 and R3.6.1 software. Results A total of 27 randomized controlled trials involving 2,210 patients were included. Bayesian NMA showed that manual acupuncture combined with conventional therapy, moxibustion combined with conventional therapy, manual acupuncture, and electroacupuncture were most effective in improving the MMSE score. The most effective interventions related to the MoCA score were moxibustion combined with conventional therapy, followed by manual acupuncture combined with conventional therapy, acupressure combined with conventional therapy, and manual acupuncture combined with moxibustion. Manual acupuncture combined with moxibustion was dominant in the cluster ranking. The results of the node splitting method revealed that direct and indirect evidence were consistent (P > 0.05). In addition, publication bias was detected. Conclusion This research will add to the body of knowledge about the safety and efficacy of acupuncture-related therapies in the treatment of mild cognitive impairment. The results of this study will also assist in the choice of clinical guidelines that optimize acupuncture treatment for patients with mild cognitive impairment.